Cross-cultural adaptation and validation of the International Knee Documentation Committee Subjective Knee Form in Greek - Koumantakis, George A. (J Orthop Traumatol, 2015)
BACKGROUND: Patient-reported outcomes require validation in a particular language and culture before administration for clinical use. MATERIALS AND METHODS: A systematic translation of the IKDC Subjective Knee Form was initially tested in 30 patients with various knee pathologies to develop the first Greek version (IKDC/SKF-GR). It was then administered to another 80 patients. The test–retest reliability (n = 35) and internal consistency (n = 80) were examined. Construct validity was tested by correlating the IKDC/SKF-GR with the SF-36 subscales (n = 80) and content validity by measuring floor/ceiling effects. Responsiveness was measured in patients with meniscus pathology (n = 24). RESULTS: Patients filled the form without omissions/questions regarding the phrasing of items. Internal consistency was good (Cronbach’s α = 0.87) and test–retest reliability very good (ICC(2,1) = 0.95, SEM = 4.4 and SDC = 12.2). Correlations with the SF-36 subscales confirmed its construct validity. No floor/ceiling effects were recorded. The effect size was large (ES = 1.26). CONCLUSIONS: The IKDC/SKF-GR has comparable measurement properties to the original form. LEVEL OF EVIDENCE: Level II.